”Urethral syndrome” in women - Dutkiewicz, Sławomir (Medical Studies/Studia Medyczne, 2013)
A contemporary overview of knowledge is presented on the subject of the so-called urethral syndrome in women, the causes of which have yet to be clearly identified. For practical reasons, the following three forms of the syndrome have been distinguished: interstitial cystitis, the “infectious” form and the “clean” form. In women who do not show symptoms of inflammation of the reproductive organs, bacterial urethritis should be distinguished from the urethral syndrome by evaluating the symptoms, the bacteriological tests and the risk of infection.